Impact of Particle Sizes on Flow Characteristics of Slurry Pump for Deep-Sea Mining. (5th March 2021) - Wang, Runkun; Guan, Yingjie; Jin, Xing; Tang, Zhenji; Zhu, Zuchao; Su, Xianghui
Abstract : As the core device of the deep-sea mining transport system, the slurry pump and its internal solid-liquid two-phase flow are extremely complicated; especially, the migration characteristics of particles have a great influence on the flow and wear of the pump. In order to grasp the particle motion law inside the slurry pump, this paper took into consideration the collision effects of the particles with particles and particles with walls and calculated the unsteady flow of the solid-liquid two-phase by CFD-DEM coupling algorithm. Then, the focus was put on the spatial distribution and movement characteristics of different particle diameters (namely, 5 mm, 10 mm, and 15 mm, while volume concentration Cv is constant 5%). The results show that the stratification phenomenon gradually disappears with the increase of particle diameter, and the intensity and scale of the vortex in the guide vane also increase obviously. Besides, as the particle diameter increases, the velocity changes more drastically, and the intensity and scale of the vortex increase significantly. Under low concentration conditions, the presence of particles has a limited influence on the hydraulic performance of the pump. By comparing with the experimental results, the simulation results are in good agreement with it, which proves that the CFD-DEM simulation in this paper is effective, and the conclusions can provide theoretical support for the design and analysis of the slurry pump in engineering application.